Production of Prophylactic Nanoformulation for Dental Caries and Investigation of Its Effectiveness by In Vitro and In Silico Methods - KILINÇ Y.; Kurtur O. B.; Gok B.; KECEL GÜNDÜZ S.; ALPAY KARAOĞLU Ş.; Atali P. Y.; KARTAL M. (My University, 2025)
Background/Objectives: This study aimed to develop cinnamon bark essential oil (CEO), orange peel essential oil(OEO) and the combination of these two essential oils (OEO-CEO) loaded PLGA nanoparticles to prevent dental caries and to investigate their effectiveness in silico and in vitro methods. Methods: EO loaded PLGA nanoparticles were produced by single emulsion method. Detailed characterization studies were performed using different methods, and the controlled release profile was obtained. The antibacterial activity of the developed formulations was investigated on S. mutans and L. casei strains by in vitro and in silico methods. Additionally, the interaction mechanisms of EOs with DNA were evaluated. Results: Our findings showed that the average droplet size of EO-loaded PLGA nanoparticles varied between 243.1 +/- 0.60 nm and 219 +/- 4.49 nm, while PdI values varied between 0.069 +/- 0.039 and 0.032 +/- 0.01. In addition, the developed nanoparticles had high encapsulation efficiency (85.14% to 66.28%) and released the active ingredient in a continuous and controlled manner. Ames test showed that the genotoxicity of EOs was eliminated due to the encapsulation of EOs in PLGA nanoparticles and antibacterial tests showed that OEO-CEO-loaded PLGA nanoparticles were effective on L. casei and S. mutans. The antibacterial activity of EOs was also supported by in silico studies. Finally, it was revealed that EOs showed potential as antibacterial agents by interacting with DNA. Conclusions: The results showed that OEO-CEO-loaded PLGA nanoparticles have the potential to be a suitable nanoformulation for developing mouthwash or toothpaste for the prevention and treatment of dental caries.
Keywords: Eczacılık; Temel Eczacılık Bilimleri; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Pharmacology and Therapeutics; Basic Pharmaceutics Sciences; Life Sciences; Health Sciences; Natural Sciences; Farmakoloji Ve Eczacılık; Farmakoloji Ve Toksikoloji; Yaşam Bilimleri (Life); Pharmacology & Pharmacy; Pharmacology & Toxicology; Life Sciences (Life); Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides